Imaging lipid lateral organization in membranes with C-laurdan in a confocal microscope - Dodes Traian, Martín Miguel (2012)
Lateral organization of biological membranes is frequently studied using fluorescence microscopy. One of the most widely used probes for these studies is laurdan. The fluorescence of this probe is sensitive to the environment polarity and thus laurdan reports the local penetration of water when inserted in membranes. Unfortunately, this probe can only be used under two-photon excitation due to its low photostability. This is a very important limitation since there are just a few laboratories with capability for two-photon microscopy. In this work, we explored the performance of C-laurdan, a carboxyl-modified version of laurdan, for imaging biological membranes using a conventional confocal microscopy setup. We acquired generalized polarization (GP) images of C-laurdan inserted in giant unillamelar vesicles composed of binary mixtures of lipids and verified that the probe allows observing the coexistence of different phases. We also tested the performance of the probe for measurement with living cells and registered GP images of melanophore cells labeled with C-laurdan in which we could observe highly-ordered regions such as filopodia. These findings show that C-laurdan can be successfully employed for studies of membrane lateral organization using a conventional confocal microscope and open the possibility of studying a wide variety of membrane-related processes.